Columbia Law School Roundtable on The Future Of Capitalism. Issue 2 (10th June 2020) - Collier, Paul; Mayer, Colin; Schwartz, Alan; Bresnahan, Kristin; Pearlstein, Steve
Abstract : In this discussion that took place at Columbia Law School's Millstein Center last October (and thus well before the appearance of the coronavirus), two distinguished English academics, a Pulitzer Prize‐winning journalist, and the executive chairman of a large American investment house discussed the role of corporations in addressing the crises that periodically beset the capitalist system. Sir Paul Collier opened with the comment that, although capitalism had shown itself to be the only effective system for mass human improvement in the past 10, 000 years, it was now experiencing its "third serious derailment." In each of the first two—the first in Northern England in the 1840s and the second during the Great Depression of the 1930s—capitalism was preserved in significant part by the "moral load‐bearing" performed by private companies and citizens. For capitalism to survive this third derailment, the public and private sectors must join forces to address what Collier to sees as the most formidable economic challenge: finding ways to transport urban jobs and capabilities to rural areas still reeling from two major blows—the first, a century ago to agriculture, and the second, for the past two or three decades, to large‐scale manufacturing. Collier's Oxford colleague Colin Mayer follows by calling on public companies to formulate and state a corporate social purpose that goes beyond maximizing their own long‐run shareholder values. And to encourage and support such a practice, Mayer urges the large universal owners that own large stakes in all the world's large listed companies not only to support and applaud such statements, but to find ways to ensure that companies are living up to them. Alan Schwartz, Executive Chairman of Guggenheim Partners, responds by noting that capitalism has been forced to make major adjustments throughout its history. And consistent with Collier's observations, Schwartz argues that the global economic order should have been preparing for the past 30 or 40 years for its biggest challenge: creating a global economy dynamic enough to provide jobs for some two or three billion new unskilled workers spawned by the globalization of the world economy. The American private sector, after having lost much of its efficiency and value in the 1970s, has since used continuous restructuring to produce enormous productivity gains and value. And although generally supportive of the thinking behind the Business Roundtable's recent statement, Schwartz deplores the confusion that continues to surround the message. Those corporate leaders now endorsing the pursuit of social goals are by no means asking their shareholders to accept below‐market returns on investment. In well‐run companies focused on long‐run efficiency and value, there is no inherent conflict between the interests of shareholders and the long‐run interests of other major stakeholders. In such companies, customers, employees, suppliers, and local communities all end up better served.